Distribution Patterns of Iron-Oxidizing Zeta- and Beta-Proteobacteria From Different Environmental Settings at the Jan Mayen Vent Fields - Vander Roost, Jan; Daae, Frida Lise; Steen, Ida Helene; Thorseth, Ingunn Hindeness; Dahle, Håkon (Frontiers in Microbiology, 2018)
Iron oxidizers are widespread in marine environments and play an important role in marine iron cycling. However, little is known about the overall distribution of iron oxidizers within vent fields, including settings with little hydrothermal activity. Moreover, to what extent different phylogenetic groups of iron oxidizers exhibit niche specialization towards different environmental settings, remains largely unknown. Obtaining such knowledge is important in order to fully understand the impact of the activity of iron oxidizers and how they are adapted. Here, we used geochemical analyses and 16S rRNA sequencing to characterize the distribution of iron oxidizers in different environmental settings within the Jan Mayen hydrothermal vent fields (JMVFs). Putative iron oxidizers affiliated to Zetaproteobacteria and Betaproteobacteria were detected in interior parts of iron mounds, bottom seawater, basalt surfaces, and surface layers of sediments, including sites with little or no sign of hydrothermal fluid flow. The detected iron oxidizers were compared to sequence types previously observed in patchily distributed iron mats associated with diffuse venting at the JMVFs. Most OTUs of iron oxidizers reoccurred under different environmental settings, suggesting a limited degree of niche specialization. Consequently, most of the detected iron oxidizers seem to be generalists with a large habitat range. Our study highlights the importance of gathering information about the overall distribution of iron oxidizers in hydrothermal systems to fully understand the role of this metabolic group regarding cycling of iron. Furthermore, our results provide further evidence for the presence of iron-oxidizing members of Betaproteobacteria in marine environments.